2020
DOI: 10.1007/s10353-020-00657-w
|View full text |Cite
|
Sign up to set email alerts
|

Closed-incision negative-pressure wound management in surgery—literature review and recommendations

Abstract: Summary Background Wound healing deficits and subsequent surgical site infections are potential complications after surgical procedures, resulting in increased morbidity and treatment costs. Closed-incision negative-pressure wound therapy (ciNPWT) systems seem to reduce postoperative wound complications by sealing the wound and reducing tensile forces. Materials and methods We conducted a collaborative English literature review in the PubMed database including publications from 2009 to 2020 on ciNPWT use in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Depending on the postinterventional bleeding from the wound, repetitive changes are necessary within the first 5 days after surgery (11,15,16). Thus, not only does the microenvironment of the wound gets disrupted but a change of dressing is done at the bedside under semi-sterile circumstances, which leads to a higher risk of surgical-site infection (1,17). iNPWT is applied directly after surgery, which guarantees for more sterility and does not need a change of dressings mostly within the first 4-5 days after surgery (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the postinterventional bleeding from the wound, repetitive changes are necessary within the first 5 days after surgery (11,15,16). Thus, not only does the microenvironment of the wound gets disrupted but a change of dressing is done at the bedside under semi-sterile circumstances, which leads to a higher risk of surgical-site infection (1,17). iNPWT is applied directly after surgery, which guarantees for more sterility and does not need a change of dressings mostly within the first 4-5 days after surgery (18).…”
Section: Discussionmentioning
confidence: 99%
“…Lower extremity amputation bears a high risk for postsurgical wound infections (1). Multi-morbid patients with diabetes-induced peripheral arterial disease represent the main subjects of major lower limb amputations (2).…”
Section: Introductionmentioning
confidence: 99%
“…Our study findings add to the body of literature on this topic. Several studies have shown promising results with ciNPT for general wound management [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Smolle et al demonstrated a reduction in wound complications in patients who received ciNPT for orthopaedic surgical sites (total joint arthroplasty) and colorectal laparotomy sites [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown promising results with ciNPT for general wound management [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Smolle et al demonstrated a reduction in wound complications in patients who received ciNPT for orthopaedic surgical sites (total joint arthroplasty) and colorectal laparotomy sites [ 14 ]. A randomised control trial conducted by Tanaydin et al compared ciNPT with standard adhesive dressings (fixation strips) in breast reduction mammoplasty surgical sites and found that ciNPT was associated with reduced wound complications ( p < 0.04) and an improvement in scar quality [ 17 ].…”
Section: Discussionmentioning
confidence: 99%